In vivo Molecular Signatures of Cervical Spinal Cord Pathology in Degenerative Compression - Horak, Tomas; Horakova, Magda; Svatkova, Alena; Kadanka, Zdenek; Kudlicka, Petr; Valosek, Jan; Rohan, Tomas; Kerkovsky, Milos; Vlckova, Eva; Kadanka, Zdenek; Deelchand, Dinesh K; Henry, Pierre-Gilles; et al. (Journal of neurotrauma, 2021)
Degenerative cervical myelopathy (DCM) is a severe consequence of degenerative cervical spinal cord (CSC) compression. The non-myelopathic stage of compression (NMDC) is highly prevalent and often progresses to disabling DCM. This study aims to disclose markers of progressive neurochemical alterations in NMDC and DCM by utilizing an approach based on state-of-the-art proton magnetic resonance spectroscopy (1H-MRS). Proton-MRS data were prospectively acquired from 73 participants with CSC compression and 47 healthy controls (HCs). The MRS voxel was centered at the C2 level. Compression-affected participants were clinically categorized as NMDC and DCM, radiologically as mild (MC) or severe (SC) compression. CSC volumes and neurochemical concentrations were compared between cohorts (HC vs. NMDC vs. DCM and HC vs. MC vs. SC) with general linear models adjusted for age and height (pFWE < 0.05) and correlated to stenosis severity, electrophysiology, and myelopathy symptoms (p < 0.05). Whereas the ratio of total creatine (tCr) to total N-acetylaspartate (tNAA) increased in NMDC (+11%) and in DCM (+26%) and SC (+21%), myo-inositol/tNAA, glutamate + glutamine/tNAA, and volumes changed only in DCM (+20%, +73%, and -14%) and SC (+12%, +46%, and -8%, respectively) relative to HCs. Both tCr/tNAA and myo-inositol/tNAA correlated with compression severity and volume (-0.376 < r < -0.259). Myo-inositol/tNAA correlated with myelopathy symptoms (r = -0.670), whereas CSC volume did not. Short-echo 1H-MRS provided neurochemical signatures of CSC impairment that reflected compression severity and clinical significance. Whereas volumetry only reflected clinically manifest myelopathy (DCM), MRS detected neurochemical changes already before the onset of myelopathy symptoms.
Keywords: kreatin; komprese míchy; Male; Inositol; inositol; krční mícha; Adult; Cervical Cord; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; Severity of Illness Index; Aspartic Acid; Cervical Vertebrae; Glutamic Acid; Creatine; myelopathy; kyselina asparagová; lidé; ženské pohlaví; studie případů a kontrol; Humans; Sensitivity and Specificity; senzitivita a specificita; cervical spinal cord, compression, degenerative; krční obratle; spectroscopy; stupeň závažnosti nemoci; Female; magnetic resonance; lidé středního věku; kyselina glutamová; Spinal Cord Compression; Middle Aged